Implementation of a One-Time Token for PDF Document Security Based on AES-128 Encryption: Rekaya Keamanan Siber - Hermansyah Syah; Desyderius Minggu; Asep Suryanta (Jurnal Telkommil, 2025)
Digital document security has become a crucial aspect in preventing unauthorized access to sensitive information. This study proposes and implements a hybrid security model for PDF documents that integrates AES-128 encryption with a One-Time Token (OTT) mechanism as a dynamic access key operating in a local environment. The research method employed is software engineering using a prototyping approach combined with quantitative experimental testing. The evaluation results indicate that the system consistently achieves an access denial rate exceeding 96.7% across all unauthorized access scenarios, including replay attacks and expired token usage. In terms of performance, the system demonstrates high efficiency, with an average encryption time of 2.61 seconds for a 10 MB file. Although performance limitations were observed for extremely large files (~1 GB), this study concludes that the proposed model is an effective, reliable, and practical solution for enhancing the security of digital document distribution without relying on cloud infrastructure.